Perancangan Ulang UI/UX Dengan Penerapan Metode Design Thinking Pada Aplikasi M-Paspor - Khoirunnisa Khoirunnisa; Isa Faqihuddin Hanif (Bulletin of Computer Science Research, 2025)
M-Paspor is a digital application developed by the Directorate General of Immigration to facilitate the online passport application process. Based on initial evaluation results using the System Usability Scale (SUS) method, the application scored 28,5, which is still below the usability standard of 68. Therefore, the objective of this study is to redesign the user interface and user experience (UI/UX) using the Design Thinking approach, which includes the stages of empathize, define, ideate, prototype, and test. After the redesign, the SUS scored increased to 81,4, falling into the “good” category, indicating that the user experience has improved. The results demonstrate that Design Thinking techniques can comprehensively identify user needs and generate more efficient, user-friendly design solutions that meet user expectations for public service applications.